Automatic Classification of Defective Photovoltaic Module Cells in Electroluminescence Images - Açıkgöz, Hakan; Korkmaz, Deniz (Fırat University, 2022)
Detection and classification of faults in photovoltaic (PV) module cells have become a very important issue for the efficient and reliable operation of solar power plants. In this study, an efficient convolutional neural network (CNN) model is proposed for fast and accurate detection and classification of faults in PV module cells. The proposed model is developed with SqueezeNet, which has fewer parameters and model size, using the transfer learning approach. In order to improve the training convergence and increase the classification performance, the activation functions of the proposed model are changed and skip connections are added from the fire modules. A dataset obtained from Electroluminescence (EL) images are used in the experiments. Data augmentation techniques are also applied to eliminate the imbalance of class distribution and increase the class samples. The performance of the proposed method is compared with pre-trained CNN architectures such as AlexNet, ShuffleNet, GoogLeNet, and SqueezeNet. In the experimental studies, the accuracy, precision, sensitivity, specificity, and F1-score values of the proposed method are obtained as 91.29%, 84.21%, 89.72%, 92.04%, and 86.88%, respectively. In addition, the proposed method improves the accuracy values of the other methods between 0.99% and 6.29%. When all the obtained results are analyzed, it is observed that the proposed method has a superior performance in the detection of faults in PV module cells.

Fotovoltaik (FV) panel hücrelerindeki arızaların tespiti ve sınıflandırılması güneş enerjisi santrallerinin verimli ve güvenilir bir şekilde işletilebilmesi için oldukça önemli bir konu haline gelmiştir. Bu çalışmada, FV panel hücrelerindeki arızaların hızlı ve doğru bir şekilde tespit edilmesi ve sınıflandırılması için etkin bir evrişimli sinir ağı (ESA) modeli önerilmiştir. Önerilen model, daha az parametre ve model boyutuna sahip SqueezeNet ile transfer öğrenme yaklaşımı kullanılarak geliştirilmiştir. Eğitim yakınsamasını iyileştirmek ve sınıflandırma başarımını arttırmak için modelin aktivasyon fonksiyonları değiştirilerek ateşleme modüllerinden atlama bağlantıları oluşturulmuştur. Deneylerde, elektrolüminesans (EL) görüntülerden elde edilen bir veri seti kullanılmıştır. Sınıf dağılımının dengesizliğini gidermek ve örnek sayısını arttırmak için veri artırma teknikleri uygulanmıştır. Önerilen yöntemin performansı AlexNet, ShuffleNet, GoogLeNet ve SqueezeNet gibi ön eğitimli ESA mimarileri ile karşılaştırılmıştır. Gerçekleştirilen deneysel çalışmalarda önerilen yöntemin doğruluk, kesinlik, duyarlılık, özgüllük ve F1-skor değerleri sırasıyla %91.29, %84.21, %89.72, %92.04 ve %86.88 olarak elde edilmiştir. Ayrıca, önerilen yöntem diğer yöntemlerin doğruluk ölçütündeki değerlerini %0.99 ile %6.29 arasında iyileştirmiştir. Elde edilen tüm sonuçlar analiz edildiğinde, önerilen yöntemin FV panel hücrelerindeki arızaların tespitinde etkili bir performansa sahip olduğu gözlemlenmiştir.
Elektrolüminesans Görüntülerde Arızalı Fotovoltaik Panel Hücrelerin Evrişimli Sinir Ağı ile Otomatik Sınıflandırılması
Keywords: Engineering; Mühendislik